Psychological Impact of the Covid-19 Pandemic on Health Workers: Literature Review - Novela Eka Candra Dewi (GLOBAL HEALTH SCIENCE GROUP, 2022)
During covid-19 pandemic, health workers are the frontline in handling this case. This study aims to evaluate the impact of covid-19 on health workers psychology. Articles were collected through the ScienceDirect, PubMed, CochraneLibrary, and SpringerLink database published between 2019-2020. Keywords used Medical staff AND Covid-19 AND Psychological impact. Articles were found based on keywords and continued with removing duplicate articles, screening titles and abstracts. Researchers only found 4 suitable and identical journals. Health workers experience psychological disorders, ranging from mild to severe. These are personal safety concerns, family worries, patient death concerns, lack of protective equipment, and fatigue due to increased working hours. Coping strategies are important for reducing stress on health workers, such as consulting with a psychiatrist, the availabilty of complete self-protection tools, and social support.